#followthebottle a mass media campaign on educating drivers about the anti-drunk driving law while addressing the increasing alcohol-related road crashes in Metro Manila - Soon, Mojahed Ariel T.
The levels of road crashes or accidents have been rising since 2012 by almost a hundred every year even with the recent implementation of the anti-drunk driving law in 2013. With the increasing sales of alcohol products and motor vehicles, drinking and driving of drivers became much more probable.